EXPLORING THE IMPACT OF VARIOUS FORMS OF BULLYING ON LEARNING MOTIVATION AMONG SENIOR HIGH SCHOOL STUDENTS - Togatorop, Widitya Ningsih; Prayuda, Meikardo Samuel; Ginting, Fiber Yun Almanda (JURNAL DARMA AGUNG, 2024)
This research delves into the relationship between bullying and learning motivation among eleventh-grade students at SMA Negeri 1 Siempat Nempu. Employing quantitative analysis, data was collected through questionnaires to assess the prevalence of bullying behaviors and their impact on students' motivation to engage in learning activities. The study begins with a demographic profile of the participants, followed by descriptive and inferential statistical analyses. While no significant correlation between bullying and learning motivation was found, the study underscores the complex interplay between these constructs. It emphasizes the importance of addressing bullying behaviors within schools and promoting supportive learning environments to enhance students' academic engagement and well-being. The findings advocate for proactive measures to prevent bullying and foster positive social interactions, ultimately aiming to create safer and more conducive learning environments for all students.